Analisis Peran Perceived Usefulness, Perceived Enjoyment, dan Privacy Concern terhadap User Satisfaction serta Continuance Intention pada Pengguna Aplikasi DANA di Jakarta - Indria Widya Dhana; Usep Suhud; Ivan Putranto (Indo Publishing, 2026)
This study aims to analyze the role of perceived usefulness, perceived enjoyment, and privacy concern on user satisfaction and continuance intention among DANA application users in Jakarta. The study employed a quantitative approach with a survey method involving 200 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that perceived usefulness and perceived enjoyment have a positive and significant effect on user satisfaction and continuance intention. Conversely, privacy concern has a negative and significant effect on user satisfaction and continuance intention. User satisfaction also has a positive and significant effect on continuance intention. The model explains 51.5% of the variance in user satisfaction and 60.8% of the variance in continuance intention. These findings confirm that functional benefits, enjoyable experiences, and privacy protection are crucial factors in determining user satisfaction and continuance intention in e-wallet applications. This study contributes to the understanding of consumer behavior in digital financial services, particularly in the context of e-wallet continuance usage, and provides practical implications for e-wallet providers to enhance user retention strategies